DEVELOPMENT OF WEATHER BOX LEARNING MEDIA ON A WEATHER THEME IN CLASS III OF PRIMARY SCHOOL - Annisa Fitria; Dinda Yarshal (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research is a type of research that develops theory (research and development) by referring to the ADDIE model which is an extension of Analysis, Design, Development, Implementation, Evaluation. The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative. media expert validation results obtained a percentage of 80%. This percentage includes "valid" criteria for use as media in learning activities for third grade elementary school students with the weather theme of science learning. Based on the results of material validation, the percentage was 82.5%. This percentage includes the criteria of "very suitable" to be used as media in learning activities for third grade elementary school students with the weather theme of science learning. Based on the results of the practicality test, the teacher's response rate was 85%. This percentage includes the "very valid" criteria for use as media in learning activities for third grade elementary school students with the weather theme of science learning. The results of this development show that the use of media in learning is very necessary. This is because it is very helpful in delivering material, especially thematic learning on the weather theme, science learning in class III elementary school